Methodological K/nots: Designing Research on the Enforcement of Labor Standards. (April 2018) - Mirchandani, Kiran; Vosko, Leah F.; Soni-Sinha, Urvashi; Perry, J. Adam; Noack, Andrea M.; Hall, Rebecca Jane; Gellatly, Mary
This article traces methodological discussions of a multidisciplinary team of researchers located in universities and community settings in Ontario. The group designed and conducted a research project on the enforcement of labor standards in Ontario, Canada. Discussions of methodological possibilities often began with "nots"—that is, consensus on methodological approaches that the team collectively rejected. Out of these discussions emerged suggestions and approaches through which we navigated dilemmas in research design. The purpose of this article is to illustrate the following: (a) epistemological tensions around mixed methods and the politics of mixing, (b) the attempt to capture the relationships between research and its impact, and, (c) the need to develop interviews which both establish respondents as knowers, and simultaneously focus on that which is unsaid/normalized.